Identifying motivators and barriers of selling used smartphones to a refurbishing business - Mieskonen, Otso (My University, 2021)
Over the past decade the refurbished smartphone market has grown from practically nothing into a significant industry. Yet, there is still a lot of room to grow, as only 12 to 15 % of used phones are recycled and the limiting factor of the refurbished smartphone market does not seem to be lack of demand, but lack of sufficient supply. Reverse supply chain management has been a topic of interest over the past decade, yet understanding consumer selling behavior, the first step of the value extraction process and in some cases the main driver of a reverse supply chain, has been mostly ignored. This study draws from existing literature related to the smartphone refurbishing industry, product acquisition management and consumer disposition behavior and aims to add to the literature by providing insight into consumer behavior related to selling used smartphones. This study answers the following research questions: what barriers exist in the way of potential sellers of used smartphones? (RQ1) Why have consumers who have sold their used smartphone decided to sell their smartphone? (RQ2) How can a smartphone refurbishing business improve the rate at which interested sellers sell their used smartphones? (RQ3) To answer the research questions data was gathered through three different sources. Firstly, an exit-intent survey was created to identify why potential sellers had stopped the process before committing to selling by sending a selling form. Second, a callback survey was completed to understand why consumers who had already decided to sell by sending the selling form had failed to send their phones and complete the selling process. Third, to understand what motivated successful sellers to sell an email survey was completed. Sellers were asked why they sold their phones, why they chose to sell to the case company, which parts of the process were sources of hesitation, and how they would improve the process. The results demonstrate that the largest reason for selling a used smartphone is the act of purchasing a new smartphone. When deciding who to sell the used smartphone to, the results indicate that trustworthiness of the purchaser, speed and clarity of the process, and purchase price are all considered important factors. When it comes to barriers to selling, insufficient price was the most significant identified barrier for consumers who left the selling website without sending the selling form, accounting for 70,0 % of the total answers (n = 417). For consumers who had sent the selling form but failed to send their phone, the largest identified barriers were ”lack of urgency”, ”issues with packing and sending the device”, and ”mistakes in the flow of information”, together accounting for 80,6 % of the responses (n = 375). Taking these findings into account may be helpful in designing the C2B selling process.

Tehdashuollettujen älypuhelinten markkina on kasvanut lähes nollasta merkittäväksi markkinaksi viimeisen kymmenen vuoden aikana. Kasvupotentiaalia riittää edelleen, sillä vain 12–15 %:ia käytetyistä puhelimista kierrätetään, ja tehdashuollettujen puhelinten markkinan rajoittaja ei vaikuta olevan kysynnän puute, vaan käytettyjen puhelinten saatavuuden puute. Palautuslogistiikan johtaminen on ollut suosittu tutkimusaihe edellisen ja kuluvan vuosikymmenen aikana, mutta siihen liittyvän kuluttajien myyntikäyttäytymisen ymmärtäminen on jäänyt vähälle huomiolle huolimatta siitä, että kuluttajilta tuotteiden hankkiminen on palautuslogistiikan arvonluontiprosessin ensimmäinen vaihe ja joidenkin toimitusketjujen tärkein ajuri. Tämä tutkimus vetää yhteen havaintoja tehdashuollettuihin puhelimiin, käytettyjen tuotteiden hankintaan ja kuluttajien tuotteiden hävittämiseen liittyvään käyttäytymiseen liittyvästä kirjallisuudesta ja pyrkii kehittämään näitä alueita keskittymällä kuluttajien käytettyjen tuotteiden myyntiin. Tämä tutkimus vastaa seuraaviin tutkimuskysymyksiin: Mitä esteitä käytettyjen älypuhelinten myyntiprosessissa on? (TK1) Miksi puhelimensa myyneet kuluttajat ovat päättäneet myydä puhelimensa? (TK2) Miten tehdashuollettuja puhelimia myyvä yritys voi parantaa myynnistä kiinnostuneiden asiakkaiden myyntiastetta? (TK3) Tutkimuskysymyksiin vastaamista varten toteutettiin kolme kyselytutkimusta. Ensimmäinen kyselytutkimus pyrki tunnistamaan miksi mahdolliset myyjät lopettavat myyntiprosessin kesken ennen myyntilomakkeen lähettämistä. Toinen kyselytutkimus pyrki luomaan ymmärrystä siitä, miksi asiakkaat, jotka olivat täyttäneet myyntilomakkeen eivät olleet lähettäneet puhelintaan. Kolmas kyselytutkimus pyrki ymmärtämään, miksi puhelimensa onnistuneesti myyneet asiakkaat olivat päättäneet myydä, miksi he päättivät myydä puhelimensa tapausyritykselle, kohtasivatko he myyntiprosessissa jotain mikä oli lähellä muodostua myynnin esteeksi, ja mitä nämä asiakkaat parantaisivat myyntiprosessissa. Tulokset osoittavat, että suurin syy käytetyn puhelimen myyntiin on uuden puhelimen ostaminen. Kun kuluttaja päättää kenelle puhelimensa myy, tulokset viittaavat siihen, että hinta, luotettavuus, nopeus ja prosessin selkeys ovat kaikki tärkeitä tekijöitä. Liian pieneksi koettu hinta oli suurin myyntilomakkeen lähettämisen este, muodostaen 70,0 %:ia tapauksista (n = 417). Niiden asiakkaiden kohdalla, jotka olivat lähettäneet myyntilomakkeen, mutta eivät olleet lähettäneet puhelimiaan, suurimmiksi esteiksi havaittiin kiireettömyys, ongelmat puhelimen pakkaamisessa ja lähettämisessä sekä väärinymmärrykset ja virheet informaation kulussa. Nämä tekijät muodostivat yhteensä 80,6 %:ia tapauksista (n = 375). Näiden löydöksien huomioiminen voi olla hyödyllistä C2B myyntiprosessin kehittämisessä.
Keywords: smartphone refurbishing, product acquisition management, C2B, consumer selling behavior